Major CYP450 Polymorphism among Saudi Patients - Almeman, Ahmad A (Drug metabolism letters, 2021)
Cytochrome P450 (CYP) contributes to a huge collection of medicinal products' Phase I metabolization. We aimed to summarize and investigate the current evidence regarding the frequency of CYP2D6, CYP2C9, CYP2C19, and MDR1 in Saudi Arabia. A computerized search in four databases was done using the relevant keywords. The screening process was done in two steps; title and abstract screening and full-text screening. Data of demographic and characteristics of included studies and patients were extracted and tabulated. Ten studies were eligible for our criteria and were included in this systematic review. The age of participants ranged between 17-65 years. Only two subjects showed PM phenotype of CYP2C19 in the Saudi population. The most frequent alleles were CYP2C19*1 (62.9%), CYP2C19*2 (11.2%-32%), and CYP2C19*17 (25.7%). The CYP2C19 was observed in 97 cases of extensive metabolizing (EM) phenotype CYP2C19. Concerning the CYP2C9, the most frequent alleles were CYP2C9*1 and CYP2C9*2, and the most frequent genotype was CYP2C9*1*1. The CYP2D6*41 allele and C1236T MDR1 were the most frequent allele in this population. The current evidence suggests that Saudi resembled European in the frequency of CYP2C19, Caucasians in both the incidence of CYP2C9 and CYP2C19 , and the absence of CYP2C19 . The CYP2D6*41 allele frequency in Saudi is relatively high. We recommend further research to evaluate the basic and clinical relevance of gene polymorphism in such ethnicity.